Struktur Sosial, Politik, dan Budaya dalam Novel Koplak Karya Oka Rusmini: Kajian Strukturalisme Genetik - Julianti Julianti; Juanda Juanda; Suarni Syam Saguni (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to reveal the author's worldview in the novel Koplak by Oka Rusmini using Lucient Goldmann's genetic structuralism study. This study uses a qualitative method that is descriptive in nature. The data collection technique used is an analysis technique that involves identification, grouping, and data analysis. The data used is in the form of language exposure, namely words, phrases, sentences, and descriptions from the novel Koplak by Oka Rusmini, published by PT Gramedia Widiasarana Indonesia in 2019. The focus of the study covers three main topics of discussion. (1) human facts in the context of social facts, (2) collective subjects, (3) the author's worldview. The results of this study reveal human facts related to social, political, economic and cultural facts. The collective subjects contained are in the form of collective consciousness from the lower class, women in a patriarchal culture and the political elite. Meanwhile, the author's worldview highlights social issues that form a complex unity of politics, economics, and culture in the novel Koplak by Oka Rusmini.